2019
DOI: 10.3390/su11185086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Severe Water Stress on Maize Growth Processes in the Field

Abstract: In this study, we investigated the effects of water stress on the growth and yield of summer maize (Zea mays L.) over four phenological stages: Seedling, jointing, heading, and grain-filling. Water stress treatments were applied during each of these four stages in a water-controlled field in the Guanzhong Plain, China between 2013 and 2016. We found that severe water stress during the seedling stage had a greater effect on the growth and development of maize than stress applied during the other three stages. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 52 publications
6
81
0
1
Order By: Relevance
“…In turn, and in line with observations (e.g. Cavero et al 2000, Heggenstaller et al 2009, Feng et al 2019, Song et al 2019, the total crop biomass b in each farm grows exponentially during the main growing season, with rate g, i.e. (Vico and Porporato 2013),…”
Section: Crop Development and Yieldsupporting
confidence: 82%
“…In turn, and in line with observations (e.g. Cavero et al 2000, Heggenstaller et al 2009, Feng et al 2019, Song et al 2019, the total crop biomass b in each farm grows exponentially during the main growing season, with rate g, i.e. (Vico and Porporato 2013),…”
Section: Crop Development and Yieldsupporting
confidence: 82%
“…Inadequate available soil water reduces the metabolic activity of maize, decreases its dry matter accumulation, and reduces its photosynthetic level by reducing the chlorophyll content in leaves. These changes eventually lead to a loss in maize yield 45 . Further, water stress had a greater effect on the growth and development of maize through the seedling stage than the other three stages.…”
Section: Discussionmentioning
confidence: 99%
“…Zarabi, Allah Dadi, Akbari, Irannejad, and Akbari (2010) also suggested that under conditions of water stress, the negative impacts of stress can be reduced through fertilizer management. Studies by other researchers also show that water stress greatly reduces maize grain yield (Song, Jin, & He, 2019). Seasonal drought is one of the most important factors limiting maize production in the world, with global maize yield diminishing by a mean of 17% each year, though in some areas up to 70% has been reported (Dastbandan Nejad, T, Saki., & Lack, S., 2010).…”
Section: Grain Yieldmentioning
confidence: 98%
“…Iron is an essential and micronutrient in plants whose deficiency due to reduced chlorophyll content of leaves leads to reduced photosynthesis and rate of carbon dioxide fixation per unit area of the leaf surface (Bisht, Nautiyal, & Sharma, 2002). Nanoparticles foliar application is a useful and effective solution to resolve iron deficiency due to the solubility and greater chance of these particles colliding with the plant (Salehi & Tamaskoni, 2008), high rate of absorption efficiency as well as surface area compared to conventional forms (Monica & Cremonini, 2009).…”
Section: Introductionmentioning
confidence: 99%